Value Chain Approach to Poverty Reduction among the Household of Lagelu Local Government Area of Oyo State - AKINNIRAN, Nuraeni Taiwo; Abidogun, D. J. (Advances in Social Sciences Research Journal, 2015)
It is highly sympathetic that with all the programmes (National Poverty Eradication Programme (NAPEP), Family Support Programme (FSP), Green Revolution, Operation Feed the Nation (OFN), National Directorate for Employment (NDE), Youth Empowerment Scheme (YES), Family and Economic Advancement Programme (FEAP), Micro Credit Scheme, Better Life programme (BLF), Directorate for Food Road and Rural Infrastructure (DFRRI) and FADAMA etc.) we have had and the huge sum of money realized from the oil industry, the poverty level of Nigeria has kept on increasing on a daily basis. Poverty level as released by the Federal Office of Statistics (FOS) has increased, from 28% in 1980, 46% in 1985, it reduced to 43% in 1992 and stood at 66% presently. Poverty is the condition whereby someone cannot access at least the three basic needs of life: housing, feeding and clothing to a comfort level. Hence this research work centred on value chain approach to Poverty Reduction and Development of livelihoods to study the causes of the failure of all these programmes and the level of impact on the people. Primary data were collected from 140 respondents through multistage sampling procedure among household living in Lagelu Local Government Area, Oyo State. Both descriptive and inferential statistics were employed to analyze the data collected. The descriptive statistical used include frequency, percentage, mean and tables to present the socio-economic characteristics of the respondents, while the inferential statistic such as Ordinary Least Square (OLS) regression model and binomial logit regression model were used to find the relationship between dependent and independent variables and test for the hypotheses. The best poverty alleviation programme in the area is FADAMA because of good implementation and monitoring while OFN is the most failed programme, the reason for this is unstable government policy. The result shows that only age (t = -1.736, P = 0.826) is negatively significant and education level (t = 1.812, p = 0.700) was positively significant at 10% significance level. This implies that the age is negative and education of the respondents has a positive effect on the participation of the respondents in the programmes. It is then concluded that lack of good monitoring is the major causes of failure of the programme, also the programme had little impact in the poverty level of the people and the income of the people is too small to cater for basic needs by the household. The government should encourage younger people to participate in the programmes and also promote education in the area.